This winter : a Heartstopper novella - Oseman, Alice (Scholastic Press, 2023)
"A very special Heartstopper story set over a challenging holiday season... Reuniting Tori Spring, her little brother Charlie, and Charlie's boyfriend Nick, this novella sees the Spring siblings brave a particularly difficult festive season"--